Effect of pharmacist-led interventions on blood pressure among asult Asian patients with hypertension: A systematic review and meta-analysis - Delgado, Shevvie Belle L.
Background: With the expanding role of pharmacists in patient-centered care, studies and reviews investigate its effectiveness in hypertension management; however, results show inconsistency and less generalizability in the Asian population.